1999
DOI: 10.1210/en.140.8.3720
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Gene Encoding an Oocyte Antigen Associated with Autoimmune Premature Ovarian Failure

Abstract: Autoimmune premature ovarian failure causes young women to develop menopausal symptoms and infertility. A similar syndrome appears in mice with postthymectomy autoimmune premature ovarian failure. We demonstrate that these mice develop antibodies against a 125-kDa protein located in the oocyte cytoplasm (ooplasm). By screening a mouse ovarian complementary DNA expression library with autoimmune serum, we have identified a novel mouse gene with a 3.75-kb ovarian transcript, the expression of which is restricted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 0 publications
2
34
0
1
Order By: Relevance
“…[101][102][103] Intriguingly, the major antigenic target that has been identified is a maternaleffect gene essential for embryogenesis, NLRP5 (NACHT, LRR and PYD domains-containing protein 5, also called NALP5 or MATER). 104,105 Importantly, NLRP5, which is also highly restricted in its tissue distribution, is targeted as a parathyroid antigen in APS-1 patients, many of whom also displayed hypogonadism. 106 Whether the same autoantigen is targeted in Aire-deficient mice is uncertain, although in our hands, an antigen of the predicted size for murine NLRP5 (121 kD) was not detected.…”
Section: Aire Regulates Promiscuous Gene Expression In Mtecmentioning
confidence: 99%
“…[101][102][103] Intriguingly, the major antigenic target that has been identified is a maternaleffect gene essential for embryogenesis, NLRP5 (NACHT, LRR and PYD domains-containing protein 5, also called NALP5 or MATER). 104,105 Importantly, NLRP5, which is also highly restricted in its tissue distribution, is targeted as a parathyroid antigen in APS-1 patients, many of whom also displayed hypogonadism. 106 Whether the same autoantigen is targeted in Aire-deficient mice is uncertain, although in our hands, an antigen of the predicted size for murine NLRP5 (121 kD) was not detected.…”
Section: Aire Regulates Promiscuous Gene Expression In Mtecmentioning
confidence: 99%
“…RNA concentration was quantified by absorbance at 260 nm. To perform RT-PCR, ϳ2 g of total RNA was reverse-transcribed into cDNAs with 1 g of oligo(dT) [12][13][14][15][16][17][18] using SuperScript Preamplication System (Life Technologies, Rockville, MD). To compare the expression of the mRNA of the oocyte 110-kDa Ag between samples, each sample was coamplified with hypoxanthine guanine phosphoribosyl transferase (HPRT) using PCR.…”
Section: Detection Of the 110-kda Oocyte Ag Messenger Rna By Rt-pcrmentioning
confidence: 99%
“…Mater, Floped, and Tle6 expression was observed in oocytes as early as the primary follicle stage [10,17,18]. Comparative studies showed the expression of the genes in several mammalian species, with a moderate degree of sequence conservation, suggesting the potential existence of the complex in all mammals (Table 1) [19][20][21][22].…”
Section: Role Of the Scmc In Meiotic Spindle Formation And Positioningmentioning
confidence: 99%